Hubungan Rinosinusitis Kronis dengan Tingkat Kekambuhan Asma Pada Anak - Andriansah, M.; Susianti, Susianti; Angraini, Dian Isti (Medula, 2024)
Asthma is one of the health problems that the world is fighting against, according to WHO in 2019 the global prevalence of asthma sufferers reached 262 million people with high mortality, causing 455,000 deaths. Apart from the high mortality rate, asthma also has a high morbidity rate. One of the reasons for the high morbidity rate in asthma is the high recurrence rate of asthma, which affects the productivity of asthma sufferers. In 2020, the asthma recurrence rate in adults was 40.7% and in children the asthma recurrence rate was divided into two groups based on age, namely in the under 18 age group it was 42.7% and in the under 5 year age group it was 52. 9%. There are many factors that influence the rate of asthma recurrence, namely allergic and non-allergic factors. One non-allergic factor that can trigger an asthma recurrence is an infection in the sinuses or sinusitis. The aim of this study was to determine the relationship between chronic rhinosinusitis and the rate of asthma recurrence in children. The method used was a review article by searching for articles using the keywords rhinosinusitis, asthma, asthma recurrence rate via Google Scholar and Pubmed, then the articles were reviewed and analyzed. The results of this review article are that there is a relationship between chronic rhinosinusitis and the rate of asthma recurrence in children, especially influencing the degree of asthma attacks in children.